Penggunaan Model Creative Problem Solving (CPS) untuk Meningkatkan Kemampuan Matematis Siswa - Restina, Hilda; Zubainur, Cut Morina; Yusrizal, Yusrizal (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
The purpose of this research is to describe students' mathematical problem solving abilities during learning process with Creative Problem Solving (CPS) model and simultaneously to see the improvement of problem solving ability of students. This research uses a qualitative approach together with quantitative through concurrent embedded strategy. The sample of research is 22 students of class VIII SMP Negeri 4 Pilot Aceh Tamiang. The instruments used are problem solving and semi-structured test. Data of problem solving ability of student during learning with CPS model was analyzed descriptively, while improvement of problem solving ability of student was analyzed by t-test using SPSS software version 22 for windows. The results showed that there was development of problem solving ability of students during learning with CPS model. The development of students 'problem-solving abilities is demonstrated by students' ability to understand problems, plan settlements, solve problems and re-examine them. This ability is evident at every meeting. Further research results also show there is an increase in problem solving skills of students with CPS model.